Eksplorasi Nilai-nilai Karakter dalam Tradisi Bepegelak Suku Dayak Kantuk di Dusun Nanga Danau, Desa Bika, Kecamatan Bika, Kabupaten Kapuas Hulu - Kurniati, Paskaria Erni; Bistari, Bistari; Syamsuri, Syamsuri; Imran, Imran; Tri Utami (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to find out and describe the character values ​​contained in the bepegelak tradition of the Kantuk Dayak Tribe in Nanga Danau Hamlet, Bika Village, Bika District, Kapuas Hulu Regency. The research method used is a descriptive method with a qualitative approach. The data sources in this research are Traditional Leaders, Community Leaders, and the Community. The data collection techniques used were observation, interviews and documentation. Data analysis techniques use data reduction analysis, data presentation, and drawing conclusions. The first result of this research is the process of implementing the bepegelak tradition through three stages, namely preparation, implementation and closing. The preparation stage consists of four activities, namely determining the implementation time, looking for tools and bepegelak materials, making bepegelak materials, and site preparation. The implementation stage consists of three activities, namely nipan pegelak, mapang and bedarak. The closing stage here is more of a free event where they eat and drink provided by the host, here they also chat and joke around to build friendship between local residents. There are 8 character values ​​contained in the Bepegelak Tradition of the Kantuk Dayak Tribe in Nanga Danau Hamlet, Bika Village, Bika District, Kapuas Hulu Regency, namely religious values, tolerance values, discipline values, hard work values, democratic values, friendly/communicative values, responsibility values, and honesty values. The factors that can preserve the Bepegelak Tradition of the Kantuk Dayak Tribe are the role of traditional leaders and community leaders as well as hereditary factors.